2021
DOI: 10.20944/preprints202104.0023.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Low-cost Air Purifier Prototype using a Ventilating Fan and Pump against COVID-19 and Haze Pollution

Abstract: Purpose: This study aimed to focus on the design and development of low-cost DIY air purifiers, using a ventilating fan, air pump, water pump, and an ultrasonic generator, with regard to filtration efficacy and also cost-effectiveness that can be used during the COVID-19 pandemic and haze pollution. Methods: Six types of household air purifiers, incorporating a HEPA filter, a HEPA filter & electrostatic fiber, an air pump, an air pump & ultrasonic wave, a water pump, and a water pump & … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This is why practical, affordable, and widely applicable measures are urgently needed to monitor and limit the risks of indoor transmission. Previous studies [6] have suggested the use of air purifiers (which use a fan, an air pump, a water pump, and an ultrasonic generator) to control the concentration of CO 2 [7]. These prototypes have advantages such as low manufacturing cost or easy installation but their reported performance in reducing the concentration of CO 2 is limited.…”
Section: Introductionmentioning
confidence: 99%
“…This is why practical, affordable, and widely applicable measures are urgently needed to monitor and limit the risks of indoor transmission. Previous studies [6] have suggested the use of air purifiers (which use a fan, an air pump, a water pump, and an ultrasonic generator) to control the concentration of CO 2 [7]. These prototypes have advantages such as low manufacturing cost or easy installation but their reported performance in reducing the concentration of CO 2 is limited.…”
Section: Introductionmentioning
confidence: 99%